# Opposite of exactly one

Express in logical form: There is exactly one person John likes.

Doing this out we can write it using the "There is exactly one" quantifier $\exists!$. Letting $L(x,y)$: $x$ likes $y$. This can be written as $\exists!xL(J,x)$. After seeing this I was wondering how we can negate it. If we were to not use the "There is exactly one" quantifiers it would become $\exists x\forall y(L(J,x)\land\lnot (L(J,y)\land y\neq x))$ Then if I were to negate it all we get $\forall x\exists y(\lnot L(J,x)\lor (L(J,y)\land y\neq x))$ Which to me reads as, John does not like everyone or John likes at least one person, and that person is not $x$. The negation that I have seems to lose the fact that John likes more than one person, regardless of if that person is $x$ or not. So how would I go about negating this statement? Is there a quantifier that is the opposite of $\exists!$?

• Well, you have two cases. Either there's nobody John likes or there exist two people whom John likes.
– lulu
Sep 11, 2017 at 16:44
• Note that $\exists!x\phi(x)$ is just a short form of $\exists x(\phi(x)\wedge\forall y(\phi(y)\to x=y))$. I think you can negate this. Logically I would say the opposite of "exactly one" is "any other amount than one, e.g. none, or more than one". Sep 11, 2017 at 16:45
• You are confusing a generic x with a specific specific x. You need notation for "John likes at least two people. "John likes exactly one person" means "It is not the case that John likes nobody and it is not the case that John likes at least two people". The negation is either John likes nobody or John likes at least two people. Sep 11, 2017 at 16:45
• M. Winter gives a good hint. So Joh likes at least two people can be written $\exists x,y| x \ne y \land (L(J,x) \land L(J,y))$ so $!\exists x|L(Jx)$ would be $[\forall x|\lnot(J,x)]\lor[\exists x,y| x \ne y \land (L(J,x) \land L(J,y))]$. Sep 11, 2017 at 16:52

The negation is correct, though the way you wrote it obfuscates the meaning. I believe the statements are equivalent, but the way you wrote it is less clear. For $\exists!xL(J,x)$, I'd write it as $\exists x(L(J,x)\land \forall y(L(J,y)\implies x=y))$. This gives a negation of $\forall x(\neg L(J,x)\lor \exists y(L(J,y)\land x\neq y))$.
EDIT: fleablood's comment explains your question about your own sentence. If John likes no people, then he certain doesn't like a unique person. If there is somebody he likes, say that person is $z$, then $z$ must satisfy $\exists y(\neg L(J,z)\lor (L(J,y)\land y\neq z))$. Since John likes $z$, the first part of the "or" statement cannot be satisfied, so the second must be, meaning John likes another person who is not $z$. Either way of writing the statement and its negation is accurate.
• @fleablood That's true; then we'd write it: $\forall x(\neg L(J,x)\lor \exists y(L(J,y)\land y\neq x)$. Then it has negation $\exists x(L(J,x)\land \forall y(\neg L(J,y)\lor x=y))$, which reflects the fact that $P\implies Q$ is equivalent to $\neg P\lor Q$. Sep 11, 2017 at 18:11